Pengaruh Debt To Equity Ratio, Current Ratio, Firm Size, Dan return On Asset terhadap Dividend Payout Ratio (Studi Pada Perusahaan Yang Termasuk Dalam Lq 45 Yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014) - Zein Ghozali; Sri Sutandi; Roy Saleh; Irsan; Lia Sari (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2017)
This study aims to examine the effect of debt to equity ratio, current ratio, firm size, and returnon asset to dividend payout ratio. By using 4 indicators as independent variable is debt to equity ratio, current ratio, firm size, and return on asset and dividend payout ratio as dependent variable. The sample wastested as many as 45 Companies Included in LQ 45 Listed on Indonesia Stock Exchange for 5 years from 2010 to 2014. The test was performed by using multiple linear regression analysis of SPSS for Windows Version 22.0. Based on the results of the study showed that the simultaneously independent variables have a positive and significant influence on the dividend payout ratio. Based on the results Partially, the variable debt to equity ratio, current ratio, firm size, and return on assets have a positive and significant effect on the dividend payout ratio.